Selective CW Laser Synthesis of MoS2 and Mixture of MoS2 and MoO2 from (NH4)2MoS4 Film - Noah Hurley; Bhojraj Bhandari; Steve Kamau; Roberto Gonzalez Rodriguez; Brian Squires; Anupama B. Kaul; Jingbiao Cui; Yuankun Lin (Micromachines, 2024)
Very recently, the synthesis of 2D MoS2 and WS2 through pulsed laser-directed thermolysis can achieve wafer-scale and large-area structures, in ambient conditions. In this paper, we report the synthesis of MoS2 and MoS2 oxides from (NH4)2MoS4 film using a visible continuous-wave (CW) laser at 532 nm, instead of the infrared pulsed laser for the laser-directed thermolysis. The (NH4)2MoS4 film is prepared by dissolving its crystal powder in DI water, sonicating the solution, and dip-coating onto a glass slide. We observed a laser intensity threshold for the laser synthesis of MoS2, however, it occurred in a narrow laser intensity range. Above that range, a mixture of MoS2 and MoO2 is formed, which can be used for a memristor device, as demonstrated by other research groups. We did not observe a mixture of MoS2 and MoO3 in the laser thermolysis of (NH4)2MoS4. The laser synthesis of MoS2 in a line pattern is also achieved through laser scanning. Due to of the ease of CW beam steering and the fine control of laser intensities, this study can lead toward the CW laser-directed thermolysis of (NH4)2MoS4 film for the fast, non-vacuum, patternable, and wafer-scale synthesis of 2D MoS2.